Resident perceptions about Typha angustifolia subsp. Domingensis (Pers.) Rohrb. (Typhaceae Juss.) in swampy areas at Picos-PI, Northeastern Brazil (Research, Society and Development, 2017)
The macrophytes are plants with great environmental importance, being an element of connection between the aquatic system and the terrestrial environment and are involved in the production of organic matter and cycling of nutrients. Typha angustifolia subp. domingensis (Pers.) Rohrb is a species belonging to the Typhaceae family and widely distributed in the municipality of Picos-PI. Therefore, this work aimed to ascertain the knowledge of the local population about the aforementioned macrophyte in wetland areas. Thus, through interviews, evenwith a large distribution of the plant in the locality, it was noticed that the residents are unaware of this species and lack knowledge regarding the ecological performance of the plant, as well as probable domestic uses for this vegetable. Moreover, it was denounced by the interviewees that the region suffers with the lack of commitment of the population, so that the residents themselves launch large amounts of waste, especially solid materials in the lagoon area.